Electronic structure of spherical quantum dots using coupled cluster method - Heidari, Ideh; Pal, Sourav; Pujari, B. S.; Kanhere, Dilip G. (Journal of Chemical Physics, 2007)
2, 6, 12, and 20 electron quantum dots have been studied using coupled cluster at singles and doubles level and extensive multireference coupled cluster (MRCC) method. A Fock-space version of MRCC (FSMRCC) containing single hole-particle excited determinants has been used to calculate low-lying excited states of the above system. The ionization potential and electron affinity are also calculated. The effect of correlation energy on excitation energy and charge density is shown by calculating them at the high density region (low value of density parameter r(s)) and at the low density region (high value of density parameter r(s)). (c) 2007 American Institute of Physics.

Comparative study of structural, acidic and hydrophilic properties of Sn-BEA with Ti-BEA using periodic density functional theory - Shetty, Sharan; Kulkarni, Bhakti S.; Kanhere, Dilip G.; Goursot, Annick; Pal, Sourav (Journal of Physical Chemistry B, 2008)
Periodic density functional theory has been employed to characterize the differences in the structural, Lewis acidic and hydrophilic properties of Sn-BEA and Ti-BEA. We show that the incorporation of Sri increases the Lewis acidity of BEA compared to the incorporation of Ti. Hence, the present work gives insight into the role of Sn in increasing the efficiency of the oxidation reactions. The results also justify that the percentage of Sri substituted in BEA is less than Ti. The structural analysis shows that the first coordination shell of Sri is larger than that of Ti. However, the second coordination of both sites remains the same. The water adsorption properties of these substituted zeolites are quantified. Moreover, we explain the higher Lewis acidity of Sn than the Ti site on the basis of the Fukui functions and charge population analysis.

Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics

First principles calculations of thermal, equations of state and thermodynamical properties of MgH2 at finite temperatures - Kelkar, Tuhina; Kanhere, Dilip G.; Pal, Sourav (Computational Materials Science, 2008)
We present the first principles calculations of the thermodynamical properties of magnesium hydride (MgH2) over a temperature range of 0-1000 K. The phonon dispersions are determined within the density functional framework and are used to calculate the free energy of MgH2 within the quasiharmonic approximation (QHA) at each cell volume and temperature T. Using the free energies the thermal equation of state (EOS) is derived at several temperatures. From the thermal EOS structural parameters such as the equilibrium bell volume (V-0) and elastic properties, namely, bulk modulus (K-0) and its pressure derivative (K-0(')) are computed. The free energies are also used to calculate various thermodynamical properties within QHA. These include internal energy E, entropy S, specific heat capacity at constant pressure C-P, thermal pressure P-thermal(V,T) and volume thermal expansion Delta V/V (%). The good agreement of calculated values of S and Cp with experimental data exhibits that QHA can be used as a tool for calculating the thermodynamical properties of MgH2 over a wide temperature range. P-thermal(V,T) increases strongly with T at all the volumes but it is a slowly varying function of volume for T = 298-500 K. According to Karki [B.B. Karki, Am. Miner. 85 (2000) 1447] such volume based variations can be neglected and so it is possible to estimate the thermal EOS only with the knowledge of the measured P-thermal(V,T) versus temperature at ambient pressure and isothermal compression data at ambient temperature. Temperature dependence of Delta V/V(%) shows that V-0 increased with increase in temperature. However, the percentage decrease in K-0 superseded this percentage increase in V-0 even at temperatures moderately higher than 298 K. Therefore, we suggest application of temperature (T > 298 K) as an approach to enhance the hydrogen storage capacity of MgH2 because of its better compressibility at these temperatures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: equation of state; Hydrogen storage; lattice dynamics; magnesium hydride; Thermodynamic properties

Growth and structural properties of Mg-N (N=10-56) clusters: density functional theory study - Heidari, Ideh; De, Sandip; Ghazi, S. M.; Goedecker, Stefan; Kanhere, Dilip G. (Journal of Physical Chemistry A, 2011)
Using the minima hopping global geometry optimization method on density functional potential energy surface, we have studied the structural and electronic properties of magnesium clusters for a size range of Mg-N where N = 10-56. Our exhaustive search reveals that most of our global minima are nonsymmetric in the size range above N = 20. We elucidate the evolutionary trend of the entire series and present more details about the peculiar growth of the clusters. For N> 20, it is possible to divide the cluster into two regions: the core region and the surface region. It turns out that the growth follows a peculiar cyclic pattern where the core and surface grow alternatively. The surface energy, as a function of number of atoms shows a clear signature as the number of atoms in the core increases by one. We have also carried out stability analysis and the stable sizes(magic numbers) agree very well with the experimental magic numbers reported by Diederich [J. Chem. Phys. 2011, 134, 124302]. We point out the similarities and differences between our results and sodium clusters.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.